EFFECT OF EXPOSURE TO PARTICULATE MATTER PM2.5 AND AIRBORNE HEAVY METALS ON CLEFT LIP AND/OR PALATE DISORDERS IN THE CITY OF BANDUNG - Rizka, Muzdalifah
Cleft lip and/or palate disorders have been the subject of extensive research as their etiology is multifactorial involving both genetic and environmental factors. One of the environmental factors that may have a correlation to birth defects and many health problems is PM2.5 and heavy metals in the air. In this study, primary data were collected at the study site. The data obtained were then further analyzed in the laboratory to obtain results using the gravimetric method, descriptive, environmental health risk analysis, and inferential analysis to determine the correlation between exposure to PM2.5 and heavy metals and cleft lip and/or palate disorders. Based on the results of risk characterization for PM2.5 parameters, it can be stated that 100% of case samples are in the unsafe stage while 53.33% of control samples are in the unsafe stage. The results of heavy metal risk characterization show that 100% of case and control samples are still within safe limits. Based on the correlation test, there is a strong correlation between PM2.5 with a correlation coefficient of 0.397. While for the correlation of Manganese, Nickel, Arsenic, Copper, Chromium and Lead have a positive correlation with a low relationship with a correlation coefficient below 0.5.